2021
DOI: 10.1016/j.chest.2021.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Apical Cap as a Potential Risk Factor for Pleuroparenchymal Fibroelastosis

Abstract: Pleuroparenchymal fibroelastosis (PPFE) is a progressive and frequently fatal interstitial lung disease that involves the upper lobes. Although its cause remains unknown, the histopathologic evidence underlying PPFE bears striking resemblance to that of the pulmonary apical cap (PAC), a relatively common and benign entity. We describe the case of a patient with PAC that evolved into distinctly asymmetric PPFE over 6 years after unilateral surgical lung injury.Given the histologic similarity between these two c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…With regard to low %VC and a preoperative pulmonary apical cap, patients with PPFE commonly have low %VC [ 1 , 3 , 4 , 18 ], and a pulmonary apical cap has the same histological characteristics as PPFE despite being an anatomically localized, non-progressive lesion [ 1 , 10 , 19 ]. In addition, a pulmonary apical cap has been reported to be potentially caused by ischaemia in the upper lobes and low-grade inflammation in the lung parenchyma [ 1 , 18 ] and is considered a potential risk factor for PPFE [ 20 ]. Therefore, we suppose that patients with low %VC and a pulmonary apical cap have some potential pathophysiological factors in common with those with PPFE.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to low %VC and a preoperative pulmonary apical cap, patients with PPFE commonly have low %VC [ 1 , 3 , 4 , 18 ], and a pulmonary apical cap has the same histological characteristics as PPFE despite being an anatomically localized, non-progressive lesion [ 1 , 10 , 19 ]. In addition, a pulmonary apical cap has been reported to be potentially caused by ischaemia in the upper lobes and low-grade inflammation in the lung parenchyma [ 1 , 18 ] and is considered a potential risk factor for PPFE [ 20 ]. Therefore, we suppose that patients with low %VC and a pulmonary apical cap have some potential pathophysiological factors in common with those with PPFE.…”
Section: Discussionmentioning
confidence: 99%
“…Marinescu et al . [ 10 ] recently described a patient with PAC that evolved into PPFE after lung surgery and speculated that the presence of PAC predisposes patients to PPFE development when faced with ongoing inflammatory injury. Although the insults were unidentified in patients with IPPFE and whether this apical fibrosis should be recognised as PAC or an early phase of PPFE was an intrinsic problem, we showed that half of the patients with IPPFE had apical fibrosis that did not progress long before the diagnosis.…”
mentioning
confidence: 99%